Scanning Electron Microscopy‐based palynological characterization of selected Euphorbiaceae taxa colonized in Pakistan. Issue 5 (18th November 2020) - Alyas, Tahira; Shaheen, Shabnum; Hussain, Farzeen; Harun, Nidaa; Hussain, Khadim; Sajjad, Sumera; Ahmed, Mushtaq; Khan, Farah
Abstract: The present study was carried out on scanning electron microscopic‐based palynological characterization of selected 20 Euphorbiaceae taxa. In this study, important pollen qualitative and quantitative features of selected Euphorbiaceae species such as polar diameter, equatorial diameter, P/E ratio, sculpturing of pollen, exine thickness, intine thickness, presence or absence of colpi and length of colpi, and pollen fertility were examined. Remarkable variations in these pollen characters had been observed among these species. In both polar and equatorial views, Riccinus communis L. exhibited the highest pollen size (polar = 264.1 μm, Equatorial = 270 μm), while Acalypha wilkesiana Mull Arg. showed lowest pollen size (Polar = 17 μm, Equatorial = 18.5 μm). Most of the pollen varied from oblate to spheroidal in shape. With regard to the P/E ratio, Sapium sebiferum L. Roxb showed the highest ratio while Bischofia javanica Blume showed minimum, that is, 1.18 and 0.85, respectively. Intine and exine thickness also varied. Most of the pollen grains were monade. Tricolporate, tricolpate, monocolpate, pentaporate, and polyporate pollen aperture types have been observed. Most of the plants showed regular, reticulate, and echinate pollen sculpturing. Pollen fertility also varied from species to species but most of the plant showed pollen fertility between 70 and 80%. Through this work, it has been concluded that quantitative and qualitative pollen features are helpful at the specific level as well as the generic level and can provide a fruitful taxonomic solution. Abstract : This study highlights the significance of light and scanning electron microscopy in the palynological characterization of Euphorbiaceae members. A variety of palynological characters has been observed that can be worthwhile in the identification and delimitation of studied Euphorbiaceae family.